2020
DOI: 10.3389/fpsyt.2020.513536
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Causation of Abnormal Host Behavior: Toxoplasma gondii and Its Potential Association With Dopey Fox Syndrome

Abstract: likely co-infected with FoxCV and/or another co-infecting neurotropic agent. Our findings using this novel system have important implications for our understanding of both the impact of parasites on mammalian host behavior in general and, potentially, of the infectious causation of certain neuropsychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 93 publications
2
9
0
Order By: Relevance
“…For example, serological testing of schizophrenic patients and matched controls showed that schizophrenic patients more often had IgG antibodies to various coinfecting agents, including T. gondii but also Chlamydia trachomatis, human herpesvirus-6, and measles virus [37,38]. In agreement with these findings, our recent research has shown that UK foxes housed in sanctuaries with aberrant behaviours indicative of neuropsychiatric impairment have a higher prevalence of T. gondii/vulpine Circovirus (FoxCV) coinfections relative to wild foxes [64]. Thus, T. gondii infection and its interaction with other coinfecting neurotropic pathogens may be a factor contributing to the aetiology of human neuropsychiatric disorders like schizophrenia.…”
Section: And Endocrine Dysregulation Have Roles To Play In the Behavioural Changes Associated With T Gondii Infectionsupporting
confidence: 61%
“…For example, serological testing of schizophrenic patients and matched controls showed that schizophrenic patients more often had IgG antibodies to various coinfecting agents, including T. gondii but also Chlamydia trachomatis, human herpesvirus-6, and measles virus [37,38]. In agreement with these findings, our recent research has shown that UK foxes housed in sanctuaries with aberrant behaviours indicative of neuropsychiatric impairment have a higher prevalence of T. gondii/vulpine Circovirus (FoxCV) coinfections relative to wild foxes [64]. Thus, T. gondii infection and its interaction with other coinfecting neurotropic pathogens may be a factor contributing to the aetiology of human neuropsychiatric disorders like schizophrenia.…”
Section: And Endocrine Dysregulation Have Roles To Play In the Behavioural Changes Associated With T Gondii Infectionsupporting
confidence: 61%
“…TGF-β1 was higher in females with anti-Toxoplasma antibody (Abdulkhaliq1, Mohammed2 and Abbas3, 2018). A higher level of TGF-β in a pregnant female with abortion, corresponded with normal pregnant women [22].…”
Section: Discussionmentioning
confidence: 87%
“…Tachyzoites is asexual (fast-growing form), tachy means fast in greek was first named by Frenkel describing the rapidly growing stage of T.gondii which formed after ingestion of oocyst by mammalian, also known trophozoite "tachyzoites" (fast-growing form) [24].…”
Section: Tachyzoitesmentioning
confidence: 99%